2019
DOI: 10.1186/s12944-019-0958-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-traditional lipid profiles associated with ischemic stroke not hemorrhagic stroke in hypertensive patients: results from an 8.4 years follow-up study

Abstract: BackgroundStudies have shown that non-traditional lipid profiles have a better association with stroke than traditional blood lipids in clinical applications, other studies have drawn different conclusions.MethodsThis study was a large-scale study with a median follow-up of 8.4 years. The hazard ratio (HR) and 95% Confidence interval (CI) of lipid variables for risk of incident stroke were analyzed by multivariable Cox proportional hazard models.ResultsDuring the follow-up, 502 new strokes (310 ischemic, 187 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 50 publications
5
12
1
1
Order By: Relevance
“…Wang et al 2011also found that hemorrhagic stroke is inversely associated with plasma serum high density lipoprotein cholesterol (HDL-C) (32). A study of Zeng et al 2019 observed that serum HDL and ratio of LDL and HDL was not associated with hemorrhagic stroke (33). Similarly in our study we found non-significant negative correlation between serum HDL-C and hemorrhagic stroke.…”
Section: Resultssupporting
confidence: 64%
“…Wang et al 2011also found that hemorrhagic stroke is inversely associated with plasma serum high density lipoprotein cholesterol (HDL-C) (32). A study of Zeng et al 2019 observed that serum HDL and ratio of LDL and HDL was not associated with hemorrhagic stroke (33). Similarly in our study we found non-significant negative correlation between serum HDL-C and hemorrhagic stroke.…”
Section: Resultssupporting
confidence: 64%
“…Many randomized control trials demonstrated LDL as an important causal risk for the development of Ischemic stroke and reported an inverse association of LDL with the risk of hemorrhagic stroke [ 16 ]. Our study observed the null associations difference of LDL in hemorrhagic and ischemic stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies estimated that the recurrence of cerebral ischemia increases with age and the increased composition of non-traditional lipid variables values: TC/HDL-C and LDL-C/HDL-C [40]. Zheng et al showed that LDL-C, non-HDL-C and LDL-C/HDL-C are associated with the future all stroke status, and TC, LDL-C, non-HDL-C, TC/HDL-C and LDL-C/HDL-C are associated with the future ischemic stroke state [41]. Other studies show a positive relationship between cholesterol levels and the risk of IS in men, while an inverse trend between TC and the risk of hemorrhagic stroke is observed in the female group.…”
Section: Non-traditional Lipid Profiles As Stroke Predictorsmentioning
confidence: 99%